Proceedings of the 2nd Symposium on Health and Education 2019 (SOHE 2019) 2019
DOI: 10.2991/sohe-19.2019.25
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Tai Chi Exercises on the Balance, Functional Gait, and Flexibility of Elderly Filipino Males

Abstract: The objective of this study is to evaluate the effect of a 16-week Tai Chi Chuan exercise program on the balance, functional gait and sit-and-reach flexibility among selected elderly Filipino males. This research utilized a one-group pre-test and post-test quasi-experimental design. Forty healthy male Filipino respondents aged 55-60 years, with no prior experience or knowledge about Tai Chi Chuan, were recruited from an urban community in Pasay City, Philippines. All of the respondents participated in a 16-wee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 11 publications
1
5
0
Order By: Relevance
“…Accordingly, the targeted tensing of muscles and relaxing, the control of the target muscles, and the correct alignment of body segments seem crucial [60]. Therefore, it is assumed that especially the task-specific components in the Pilates interventions [13] and the flowing changes between different movements and poses of Tai Chi exercises [41, 61] mainly account for the positive effects on flexibility. Gait performance was not affected, as gait is considered a robust pattern [62] that less likely benefits from MBI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, the targeted tensing of muscles and relaxing, the control of the target muscles, and the correct alignment of body segments seem crucial [60]. Therefore, it is assumed that especially the task-specific components in the Pilates interventions [13] and the flowing changes between different movements and poses of Tai Chi exercises [41, 61] mainly account for the positive effects on flexibility. Gait performance was not affected, as gait is considered a robust pattern [62] that less likely benefits from MBI.…”
Section: Discussionmentioning
confidence: 99%
“…MBI, mind-body intervention; AC, active control; SE, standard error; IV, independent variable; CI, confidence interval; SMD, standardized mean difference. Tai Chi exercises[41,61] mainly account for the positive effects on flexibility. Gait performance was not affected, as gait is considered a robust pattern[62] that less likely benefits from MBI.…”
mentioning
confidence: 99%
“…For example, a study showed that eight-week tai chi exercise significantly improved GS, stride length, pelvic flexibility, and ankle flexibility (36). Another study reported that tai chi exercise had significant positive effects on balance, physical functioning, walking, and flexibility among elderly men (15). Similarly, a study showed that tai chi exercise was associated with significant improvements…”
Section: Discussionmentioning
confidence: 99%
“…Reduced GS is considered as a significant predictor of fall (15) and fall is a major threat to elderly people's health (16). A study showed that around 30% of elderly people above 65 years experience at least one fall incident each year (17).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation